Output Consensus of Heterogeneous Linear Multi-Agent Systems with Unbounded Distributed Transmission Delays - Bi, Cong; Xu, Xiang; Liu, Lu; Feng, Gang (IEEE Conference on Industrial Electronics and Applications (Online), 2020)
The output consensus problem of heterogeneous linear multi-agent systems subject to unbounded distributed transmission delays is considered in this paper. A novel distributed output feedback control law is proposed and it is shown that the multi-agent system can achieve output consensus by the proposed control law under some sufficient conditions. One of the distinctive advantages of this work over existing works is that there is no restriction on either eigenvalues or initial conditions of the agents in spite of the existence of unbounded transmission delays. Moreover, our results can include some existing ones on consensus control with bounded or unbounded distributed delays as special cases. Finally, the effectiveness of the proposed control law is demonstrated by two simulation examples.